Trends in Traffic Accidents of Firefighting Vehicles and Their Evaluation - Janosik, Ladislav; Sudrychova, Izabela; Janosikova, Ivana; Cochlar, Marek; Tomasek, Martin (Communications - Scientific Letters of the University of Zilina, 2023)
The Fire Rescue Service of the Czech Republic is a security force whose primary task is to protect the lives and health of the population from fire and other emergency and critical situations. Members of the Fire Rescue Service of the Czech Republic need special firefighting appliances for performing these public services. The first-response firefighting vehicles are professionally denominated as firefighting vehicles. These vehicles are used to transport units of firefighters, fire extinguishers and a technical equipment to a scene of an intervention. Traffic accidents occur occasionally while an emergency drive. Traffic accidents always have a negative economic impact on a fire protection unit and can endanger its operational capacity in the short term. This paper summarizes results of a traffic accidents analysis of a major group of emergency firefighting vehicles - water tenders.
Keywords: Fire Rescue Service of the Czech Republic; firefighting vehicles; traffic accident